PERLINDUNGAN HUKUM BAGI KORBAN CYBERCRIME PENYEBARAN DATA PRIBADI SECARA ONLINE - Apriandi, Muliawansyah; Sagala, Rotua Valentina; Basuki, Basuki (SINERGI : Jurnal Riset Ilmiah, 2024)
The current development of information technology has certainly had a huge influence on social life in Indonesia. With such rapid progress in the field of technology and information, it is like a double-edged sword because apart from having a positive impact, it can also have a negative impact, one of which is the emergence of cybercrime online dissemination of personal data. The research method used is a normative juridical research method, while technical data analysis uses a statutory approach and a case approach, as well as using legal protection theory and punishment theory. The problem formulation taken is how to regulate cybercrime victims disseminating personal data online in Indonesia and what legal protection there is for cybercrime victims disseminating personal data online in Indonesia. The research results showed that legal protection for cybercrime victims of online dissemination of personal data in Indonesia has been regulated based on Law no. 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law), whose criminal sanctions prioritize punishment for the perpetrator only to provide a deterrent effect, and have not provided a direct impact or benefit for the victim. And in order to provide human rights protection for cybercrime victims of online distribution of personal data in Indonesia, apart from being subject to imprisonment and/or fines, perpetrators may also be subject to additional penalties in the form of confiscation of profits and/or assets obtained or proceeds from criminal acts. , and payment of compensation for victims, such as additional criminal sanctions for confiscation of profits and/or assets obtained or proceeds from criminal acts and payment of compensation for victims. Thus, to realize the Integrated Criminal Justice System, law enforcers not only impose prison sanctions and/or fines on perpetrators, but can also impose additional criminal sanctions which can have a direct impact or benefit for victims. And the House of Representatives and the President need to revise the ITE Law, especially by adding additional criminal provisions in the form of confiscation of profits and/or assets obtained or proceeds from criminal acts and payment of compensation. So that this law can really provide better legal protection and can also be felt directly by victims of cybercrime spreading personal data online in Indonesia